Oral cyclophosphamide monotherapy in advanced resistant ocular cicatricial pemphigoid - Arash Maleki; Allison Richey; Hasan Bashir; Soheila Asgari; Tate Valerio; Yasmin Massoudi; Andrew Dolinko; Peter Y. Chang; C. Stephen Foster; Stephen D. Anesi (Taiwan Journal of Ophthalmology)
PURPOSE: The purpose of the study was to study the efficacy of oral cyclophosphamide monotherapy in advanced resistant ocular cicatricial pemphigoid (OCP). MATERIALS AND METHODS: This retrospective case series examines patients diagnosed with advanced resistant OCP at a uveitis tertiary care center who were treated with oral cyclophosphamide therapy. RESULTS: Seventeen patients were included in this study. The average age of the participants was 74.3 ± 10.3 years, ranging from 60 to 99 years. The gender distribution was 8 females to 9 males. Oral cyclophosphamide-induced remission in 7 patients (41.1%) and was prematurely discontinued in 10 patients (58.9%), with 7 (63.7%) citing ineffectiveness and 3 (36.3%) experiencing side effects as reasons for discontinuation. The average therapy dose of cyclophosphamide administered was 116.1 ± 47.5 mg. The average duration required for the induction of remission was 150 ± 128 days. The overall therapy duration averaged 306 ± 189 days. Conducting univariate logistic regression with generalized estimating equations (GEEs) on variables did not reveal statistically significant differences between the two groups (responsive and nonresponsive to oral cyclophosphamide therapy), except for the maximum dose of oral cyclophosphamide therapy (P = 0.007). CONCLUSION: The prognosis of advanced OCP in patients is unlikely to be altered by the stepladder approach and step-up strategy. While oral cyclophosphamide can be efficacious for remission induction in resistant and aggressive OCP cases, a step-down strategy employing less potent agents with safer side effect profiles should be contemplated for subsequent treatment.